Christian Wolff - Hicks, Michael, 1956- (Book collections on Project MUSE., 2012)
In this first interpretive narrative of the life and work of Christian Wolff, Michael Hicks and Christian Asplund trace the influences and sensibilities of a contemporary composer's atypical career path and restless imagination. Written in full cooperation with Wolff, including access to his papers, this volume is a much-needed introduction to a leading avant-garde composer still living, writing music, and speaking about his own work. _x000B__x000B_Wolff has pioneered various compositional and notational idioms, including overtly political music, indeterminacy, graphic scores, and extreme virtuosity. Hicks and Asplund cover Wolff's family life and formative years, his role as a founder of the New York School of composers, and the context of his life and work as part of the John Cage circle, as well as his departures from it. Critically assessing Wolff's place within the experimental musical field, this volume captures both his eloquence and reticence and provides insights into his broad interests and activities within music and beyond._x000B_